STUDENTS’ ERROR IN TRANSLATING ENGLISH NARRATIVE TEXT “STORY OF LAKE TOBA” INTO INDONESIAN FOR GRADE X - Debby Ayu Agustien, Iskandar Zulkarnain, Syafrina Prihatini (EXCELLENCE: Journal of English and English Education, 2021)
This research dealt with the analysis of students’ error in translating English narrative text “Story of Lake Toba” into Indonesian. The objective of the research was to find out the types of error and the dominant type of error made by the students in translating the narrative text. The population was all the students of grade X at SMA Teladan Sei Rampah academic year 2018-2019 with the total number students was 40. There were two parallel classes, namely X-IPA2 and X-IPA3. Each class consisted of 20 students. By applying cluster random sampling technique, X-IPA2 was selected to be the sample. The instrument of the research was written test in the form of essay test which was divided into 20 questions in translating. The total errors found was 65 occurrences which was consisted of error of omission = 10 (15.38%), error of addition = 13 (20%), error of misordering = 36 (55.38%), and error of misinformation = 6 (9.23%). The dominant type of error made by the students was error of misordering